2014
DOI: 10.1111/1755-0998.12360
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly of the transcriptome of Acanthaster planci testes

Abstract: A key strategy to reduce coral loss is the development of effective control method for the corallivorous crown-of-thorns sea star (Acanthaster planci), an omnipresent scourge and threat to the biodiversity of reefs in the Indo-Pacific region. Limited genetic resources are available for this highly fecund species. In this study, we explored one aspect at the heart of A. planci outbreaks, the male reproductive system. Using high-throughput sequencing technology, we report for first time the production of a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 81 publications
8
29
0
Order By: Relevance
“…From these unigenes, 60,439 (~34%) were blasted to known proteins in the public databases NCBI (nr) and UniProt (Swiss‐Prot and TrEMBL), while 116,446 (~66%) had no matches and may represent: (1) specific unigenes of M. franciscanus with unknown function; (2) sequences with low similarity to those compared in public databases; and/or (3) chimeric sequences. Although the percentage of unigenes with a BLAST‐hit may appear to be relatively low, we found that the number of unigenes with significant alignments (≤1 e −5 ) to known proteins in M. franciscanus is higher than those reported in other studies with nonmodel echinoderms (Delroisse et al., 2015; Dilly et al., 2015; Gaitán‐Espitia, et al, 2016; Gillard, Garama, & Brown, 2014; Pérez‐Portela, Turon, & Riesgo, 2016; Stewart, Stewart, & Rivera‐Posada, 2015; Vaughn, Garnhardt, Garey, Thomas, & Livingston, 2012; Zhou et al., 2014). Most of the annotated unigenes hit against the purple sea urchin Strongylocentrotus purpuratus (88.4%), followed by the acorn worm Saccoglossus kowalevskii (1.5%), and the Pacific oyster Crassostrea gigas (<1%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From these unigenes, 60,439 (~34%) were blasted to known proteins in the public databases NCBI (nr) and UniProt (Swiss‐Prot and TrEMBL), while 116,446 (~66%) had no matches and may represent: (1) specific unigenes of M. franciscanus with unknown function; (2) sequences with low similarity to those compared in public databases; and/or (3) chimeric sequences. Although the percentage of unigenes with a BLAST‐hit may appear to be relatively low, we found that the number of unigenes with significant alignments (≤1 e −5 ) to known proteins in M. franciscanus is higher than those reported in other studies with nonmodel echinoderms (Delroisse et al., 2015; Dilly et al., 2015; Gaitán‐Espitia, et al, 2016; Gillard, Garama, & Brown, 2014; Pérez‐Portela, Turon, & Riesgo, 2016; Stewart, Stewart, & Rivera‐Posada, 2015; Vaughn, Garnhardt, Garey, Thomas, & Livingston, 2012; Zhou et al., 2014). Most of the annotated unigenes hit against the purple sea urchin Strongylocentrotus purpuratus (88.4%), followed by the acorn worm Saccoglossus kowalevskii (1.5%), and the Pacific oyster Crassostrea gigas (<1%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The era of genomics on CoTS using HTS technologies has just started to emerge. By sequencing the transcriptome of the male gonad of CoTS, using an RNA-Seq approach, key candidate genes involved in reproduction were identified [263]. This study found that CoTS contain proteins, molecules, signalling pathways and key developmental genes that are known to have a role in sperm motility and signalling in other echinoderms [263].…”
Section: Genetic and Genomic Samplingmentioning
confidence: 92%
“…By sequencing the transcriptome of the male gonad of CoTS, using an RNA-Seq approach, key candidate genes involved in reproduction were identified [263]. This study found that CoTS contain proteins, molecules, signalling pathways and key developmental genes that are known to have a role in sperm motility and signalling in other echinoderms [263]. A recent study using genome sequencing and proteomics in combination with behavioral experiments, allowed the identification of key species-specific pheromones involved in their aggregation [176].…”
Section: Genetic and Genomic Samplingmentioning
confidence: 99%
“…By sequencing the transcriptome of the male gonad of CoTS, using an RNA-Seq approach, key candidate genes involved in reproduction were identified (Stewart et al 2015). This study found that CoTS contains proteins, molecules, signaling pathways and key developmental genes that are known to have a role in sperm motility and signaling in other echinoderms (Stewart et al 2015). In a recent study, using genome sequencing and proteomics in combination with behaviour experiments, allowed the identification of key species-specific pheromones involved in their aggregation .…”
Section: Genetic and Genomic Samplingmentioning
confidence: 99%
“…The era of genomics on CoTS using HTS technologies has just started to emerge. By sequencing the transcriptome of the male gonad of CoTS, using an RNA-Seq approach, key candidate genes involved in reproduction were identified (Stewart et al 2015). This study found that CoTS contains proteins, molecules, signaling pathways and key developmental genes that are known to have a role in sperm motility and signaling in other echinoderms (Stewart et al 2015).…”
mentioning
confidence: 92%